Co-destruction of value: A stakeholder conceptual review - Olabode Ogunbodede (International Journal of Business Science & Applied Management (IJBSAM), 2022)
Co-destruction of value has been highlighted as a possible outcome of every interaction between firms and consumers. Despite the likelihood of its occurrence, the concept is not adequately defined or understood, while little is known about how and where it occurs. This paper reviews the literature on co-destruction to provide insights into what co-destruction is, and it identifies where co-destruction occurs and how it occurs through resource mis-integration and in practice. The review takes a stakeholder approach, highlighting how value can be co-destroyed by stakeholders both within the dyad of the firm and its consumers and beyond this dyad during multiparty interactions and in virtual communities. The analysis suggests that value can only be co-destroyed when the expectations of the beneficiary are higher than the level of service offered by the provider. The paper proposes a new definition for co-destruction and highlights pressing research gaps within the co-destruction literature.
Keywords: 650; service-dominant logic; value co-destruction; practices; resources; value destruction; value co-creation; value creation; framework; expectations